Investigating the effects of rosmarinic acid on ovarian tissue, inflammatory markers, and sex hormones in polycystic ovary syndrome rats - Sina Vakili; Farhad Koohpeyma; Mohammad Samare‐Najaf; Bahia Namavar Jahromi; Morteza Jafarinia; Sepide Goharitaban; Amir Savardashtaki; Ali Samareh; Fatemeh Amini; Mohammad Hashem Hashempur (Physiological Reports)
Abstract Polycystic ovary syndrome (PCOS) causes the impairment of female fertility and elevates the risk of metabolic disorders. The current study aimed to evaluate the effects of rosmarinic acid (Ros) on the ovarian histo‐stereology, the level of reproductive hormones, and inflammation in a rat model of PCOS. Fifteen adult Sprague Dawley rats were randomly divided into three groups, including controls, PCOS, and PCOS+Ros (receiving 25 mg/kg of Ros for 39 days). After treatments, the ovarian histo‐stereology, the level of reproductive hormones, and the level of inflammatory markers were analyzed. PCOS led to increased ovarian weight and volume, cortical and medullary expansion, reduced ovarian follicles, and enhanced follicular atresia. It also caused hormonal imbalances, elevating LH, FSH, and testosterone while decreasing estradiol, progesterone, and AMH. Additionally, PCOS increased pro‐inflammatory markers (TNF‐α and IL‐6) and decreased anti‐inflammatory markers (IL‐4 and IL‐10). However, Ros administration in PCOS animals improved ovarian structure, increased follicle numbers, reduced atresia, balanced reproductive hormones, and restored inflammatory markers (p value <0.05). The present findings may suggest Ros as a novel strategy for the management of PCOS, although further studies are necessary.